Multiprofessional teams: understandings about work processes in the Family Health Strategy (Research, Society and Development, 2021)
The multiprofessional teams in the Family Health Strategy (FHS) still face challenges to consolidate their work, being necessary to know them, approaching the dynamics of activities of these teams. Thus, the objective was to understand the work process of the Extended Family Health and Primary Care Center (EFHPCC) and the Multiprofessional Health Residency (MHR) working in the FHS in a municipality in northeastern Brazil. This is an exploratory-descriptive study with a qualitative approach conducted in a municipality in the state of Ceará, Northeast, Brazil, from February to July 2018. Seven professionals from the EFHPCC and MHR teams participated in the study. Semi-structured interviews and focus groups were conducted to obtain the data, which were analyzed and organized into two thematic categories: multiprofessional integration and performance and municipal management involvement in multiprofessional activities. Many mismatches still emerge in the daily lives of professionals of reference and multiprofessional teams, affecting the organization and effectiveness of health care processes and management of this work. Nevertheless, teamwork is seen as quite positive by participants for the effective practice of matrix support.